Synthesis of small peptide compounds, molecular docking, and inhibitory activity evaluation against phosphatases PTP1B and SHP2 - Kostrzewa T; Sahu KK; Gorska-Ponikowska M; Tuszynski JA; Kuban-Jankowska A (Dove Medical Press, 2018)
Tomasz Kostrzewa,1 Kamlesh K Sahu,2 Magdalena Gorska-Ponikowska,1 Jack A Tuszynski,3 Alicja Kuban-Jankowska1 1Department of Medical Chemistry, Medical University of Gdansk, Gdansk, Poland; 2Department of Medical Microbiology and Immunology, University of Alberta, Edmonton, AB, Canada; 3Department of Oncology, University of Alberta, Edmonton, AB, Canada Background: The protein tyrosine phosphatases PTP1B and SHP2 are promising drug targets in treatment design for breast cancer. Searching for specific inhibitors of their activity has recently become the challenge of many studies. Previous work has indicated that the promising PTP inhibitors may be small compounds that are able to bind and interact with amino residues from the binding site.Purpose: The main goal of our study was to synthesize and analyze the effect of selected small peptide inhibitors on oncogenic PTP1B and SHP2 enzymatic activity and viability of MCF7 breast cancer cells. We also performed computational analysis of peptides binding with allosteric sites of PTP1B and SHP2 phosphatases.Methods: We measured the inhibitory activity of compounds utilizing recombinant enzymes and MCF7 cell line. Computational analysis involved docking studies of binding conformation and interactions of inhibitors with allosteric sites of phosphatases.Results: The results showed that the tested compounds decrease the enzymatic activity of phosphatases PTP1B and SHP2 with IC50 values in micromolar ranges. We observed higher inhibitory activity of dipeptides than tripeptides. Phe-Asp was the most effective against SHP2 enzymatic activity, with IC50=5.2±0.4 µM. Micromolar concentrations of tested dipeptides also decreased the viability of MCF7 breast cancer cells, with higher inhibitory activity observed for the Phe-Asp peptide. Moreover, the peptides tested were able to bind and interact with allosteric sites of PTP1B and SHP2 phosphatases.Conclusion: Our research showed that small peptide compounds can be considered for the design of specific inhibitors of oncogenic protein tyrosine phosphatases. Keywords: breast cancer, protein tyrosine phosphatase PTP1B, SHP2, peptides, PTP inhibitors